2017
DOI: 10.1371/journal.pone.0178922
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuropeptide-Y in nandrolone decanoate-induced attenuation of antidepressant effect of exercise

Abstract: Since the increased prevalence of anabolic androgenic steroids abuse in last few decades is usually accompanied by various exercise protocols, the scope of our study was to evaluate the effects of chronic nandrolone decanoate administration in supraphysiological dose and a prolonged swimming protocol (alone and simultaneously with nandrolone decanoate) on depressive state in male rats. Simultaneously, we investigated the possible alterations in neuropeptide Y (NPY) content in blood and the hippocampus, in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
4
19
1
Order By: Relevance
“…Following decapitation, rat brains (after immediate removal from the skull) proceeded previously described procedure [ 23 ]—fixation in 4% neutral buffered formaldehyde, dehydration and were embedded. 5 μm thick coronal brain sections were dewaxed, rehydrated and treated with citrate buffer (pH 6.0) in the microwave for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following decapitation, rat brains (after immediate removal from the skull) proceeded previously described procedure [ 23 ]—fixation in 4% neutral buffered formaldehyde, dehydration and were embedded. 5 μm thick coronal brain sections were dewaxed, rehydrated and treated with citrate buffer (pH 6.0) in the microwave for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…Since hippocampus plays one of the key roles in mood modulation and may be involved in control of some specific behavioral patterns [ 23 ], alterations in hippocampal PV content have been proposed as a possible explanation for exercise-induced behavioral changes. It has been reported that behavioral alterations induced by various types of exercise protocols were accompanied with specific modification in hippocampal parvalbumin expression [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ND groups (ND and E+ND) and TE groups (TE and E+TE) received 20 mg/kg subcutaneous injections of AASs (DEKA 300, SteroxLab, EU and Testosteron depo, Galenika a.d., Serbia, respectively) weekly, in a single dose, for 6 weeks. The final doses of ND and TE were chosen to mimic the doses for heavy human AASs abusers (Kanayama et al, 2008), since these were confirmed to be sufficient to induce behavioral alterations in our previous studies (Selakovic et al, 2016, 2017; Joksimović et al, 2017a,b). The exercise protocols also lasted for 6 weeks (in groups E, E+ND, and E+TE).…”
Section: Methodsmentioning
confidence: 99%
“…This test is based on the assumption that an animal will actively try to escape an aversive (stressful) stimulus (Chermat et al, 1986). The test was performed according to a previously described procedure (Joksimović et al, 2017b). The whole test trial was recorded using a video camera, and recordings were analyzed in order to determine the following parameters (data presented in Supplementary Table S1): the latency to the first immobility, the number of immobility episodes, the total duration of immobility (TDI) and the average duration of an immobility episode (the ratio of the TDI to the number of immobility episodes).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation